Skin conditions in figure skaters, ice-hockey players and speed skaters: Part II - Cold-induced, infectious and inflammatory dermatoses - Tlougan, B. E.; Mancini, A. J.; Mandell, J. A.; Cohen, D. E.; Sanchez, M. R. (Sports Medicine, 2011)
Participation in ice-skating sports, particularly figure skating, ice hockey and speed skating, has increased in recent years. Competitive athletes in these sports experience a range of dermatological injuries related to mechanical factors: exposure to cold temperatures, infectious agents and inflammation. Part I of this two part review discussed the mechanical dermatoses affecting ice-skating athletes that result from friction, pressure, and chronic irritation related to athletic equipment and contact with surfaces. Here, in Part II, we review the cold-induced, infectious and inflammatory skin conditions observed in ice-skating athletes. Cold-induced dermatoses experienced by ice-skating athletes result from specific physiological effects of cold exposure on the skin. These conditions include physiological livedo reticularis, chilblains (pernio), Raynaud phenomenon, cold panniculitis, frostnip and frostbite. Frostbite, that is the literal freezing of tissue, occurs with specific symptoms that progress in a stepwise fashion, starting with frostnip. Treatment involves gradual forms of rewarming and the use of friction massages and pain medications as needed. Calcium channel blockers, including nifedipine, are the mainstay of pharmacological therapy for the major nonfreezing cold-induced dermatoses including chilblains and Raynaud phenomenon. Raynaud phenomenon, a vasculopathy involving recurrent vasospasm of the fingers and toes in response to cold, is especially common in figure skaters. Protective clothing and insulation, avoidance of smoking and vasoconstrictive medications, maintaining a dry environment around the skin, cold avoidance when possible as well as certain physical manoeuvres that promote vasodilation are useful preventative measures. Infectious conditions most often seen in ice-skating athletes include tinea pedis, onychomycosis, pitted keratolysis, warts and folliculitis. Awareness, prompt treatment and the use of preventative measures are particularly important in managing such dermatoses that are easily spread from person to person in training facilities. The use of well ventilated footgear and synthetic substances to keep feet dry, as well as wearing sandals in shared facilities and maintaining good personal hygiene are very helpful in preventing transmission. Inflammatory conditions that may be seen in ice-skating athletes include allergic contact dermatitis, palmoplantar eccrine hidradenitis, exercise-induced purpuric eruptions and urticaria. Several materials commonly used in ice hockey and figure skating cause contact dermatitis. Identification of the allergen is essential and patch testing may be required. Exercise-induced purpuric eruptions often occur after exercise, are rarely indicative of a chronic venous disorder or other haematological abnormality and the lesions typically resolve spontaneously. The subtypes of urticaria most commonly seen in athletes are acute forms induced by physical stimuli, such as exercise, temperature, sunlight, water or particular levels of external pressure. Cholinergic urticaria is the most common type of physical urticaria seen in athletes aged 30 years and under. Occasionally, skaters may develop eating disorders and other related behaviours some of which have skin manifestations that are discussed herein. We hope that this comprehensive review will aid sports medicine practitioners, dermatologists and other physicians in the diagnosis and treatment of these dermatoses.